Bidirectional regulation of reactive oxygen species for radiosensitization in nasopharyngeal carcinoma - Jie Chen; Chengyu Feng; Yufei Lan; Xiangtian Chen; Zhengqi Peng; Zihan Huang; Ruiqing Wang; Wenxin Zhang; Yingying Ye; Zhilei Mao; Dongyue Pan; Lihua Yang (Journal of Nanobiotechnology)
Abstract Radiotherapy (RT) is the primary treatment modality for nasopharyngeal carcinoma (NPC). However, the tumor microenvironment (TME)-induced radioresistance often compromises its therapeutic efficacy. Herein, we propose an innovative bidirectional radiosensitization strategy for NPC. Specifically, we have encapsulated metformin (Met) and copper sulfide nanoparticles (CuS NPs) within injectable DNA supramolecular hydrogels (DSH) to create a novel radiosensitizer, Met-CuS@DSH. This radiosensitizer not only effectively reverses tumor hypoxia to promote reactive oxygen species (ROS) generation but also significantly inhibits glutathione (GSH)-mediated ROS scavenging, thereby achieving bidirectional radiosensitization by enhancing ROS production and suppressing its scavenging. This strategy significantly improves the therapeutic effect of NPC while reducing the RT dose (3 Gy in total), which provides a promising approach for overcoming the radioresistance of NPC caused by TME. Graphical Abstract